SSCP video course. - Harris, Shon (Pearson Certification, 2009)
"Get all the hands-on training you need to pass (ISC)2's tough SSCP exam, get certified, and move forward in your IT security career! In this online video, the world's #1 information security trainer walks you through every skill and concept you'll need to master. This online video contains over four hours of training adapted from Shon Harris's legendary five-day SSCP boot camps-including realistic labs, scenarios, case studies, and animations designed to build and test your knowledge in real-world settings!"--Resource description page